Bioaccessibility of Copper, Molybdenum and Zinc from Selected Oilseed Cakes Using Three Stage In Vitro Technique - Gupta, Shiva; Tomar, S.K.; Mani, Veena; Kumar, R. Dhinesh; Parihar, Deepti; Anjila Kujur, S.T. (Indian Journal of Animal Nutrition, 2018)
The study was conducted to determine chemical composition, in vitro dry matter digestibility (IVDMD) and bioaccessibility of (%) of copper (Cu), molybdenum (Mo) and zinc (Zn) in mustard (MC), cotton seed (CSC)and maize germ oil cake (MGOC). The values of DM, OM, CP, EE, NDF, ADF and TA in MC were 92.27, 92.43, 38.36, 8.17, 28.11, 21.32 and 7.57%, respectively and the corresponding values in CSC were 92.16, 92.91, 21.11, 6.26, 38.33, 31.14 and 7.09% and MGOC were 93.72, 96.42, 18.56, 8.86, 34.60, 23.71 and 3.58%. The MC, CSC andMGOC had Cu content of 9.87, 11.28 and 8.62 ppm, Mo content of 1.52, 1.69 and 1.12 ppm and Zn level of 58.94, 38.93 and 28.21 ppm, respectively. IVDMD (%) was found to be the highest for MC (68.42Â±0.35) and the lowest for CSC (59.71Â±1.07). Bioaccessibility (%) of Cu and Zn was lower (P